Seasonal Dynamics of Collembola (Springtail) Fauna in the Soils of Fruit Orchards National University of Uzbekistan (Texas Journal of Philology, Culture and History, 2025)
This article investigates the seasonal dynamics of Collembola fauna in the soils of fruit orchards. During the study, seasonal changes in the abundance, activity, and species composition of collembolans were analyzed throughout the year. Soil samples were collected in spring, summer, autumn, and winter, and collembolans were extracted using a Berlese–Tullgren apparatus and identified based on morphological characteristics. The results showed that the highest population densities of collembolans were recorded in spring and summer, which can be explained by favorable soil moisture and temperature conditions during these seasons. In autumn, their abundance decreased relatively, while in winter it reached minimum levels. The findings confirm that collembolans are important bioindicators for assessing soil ecological conditions. The obtained data are of scientific and practical significance for monitoring soil health, ensuring ecological sustainability, and conserving biological diversity in fruit orchard agroecosystems.